Factors can be multiplied together to get the original number.
For example here are the factors of 66.
1 and 66. 2 and 33. 3 and 22. 6 and 11.
1 multiplied by 66 results in the original number 66.
2 multiplied by 33 results in the original number 66.
3 multiplied by 22 results in the original number 66.
<span>6 multiplied by 11 results in the original number 66.</span>
Answer:
Midpoint = ( (x1+x2)/2 , (y1+y2)/2 )
Step-by-step explanation:
Please upload the line segment otherwise, you can use the equation above to solve for it.
I think you forgot to add a photo
Answer:
The answer is 1/4!
Step-by-step explanation:
1) -10x+y=4
Now, you should substitute x in every situation.
* x=-2 <em>=> -10*(-2)+y=4... 20+y=4... <u>y=-16</u></em>
<em />* x=-1 =>-10*(-1)+y=4... 10+y=4... <u>y=-6</u>
<u />*x=0 => -10*0+y=4... <u>y=4</u>
<u />* x=1 => -10*1+y=4... -10+y=4... <u>y=14</u>
<u />* x=2 => -10*2+y=4... -20+y=4... <u>y=24</u>
<u>2)</u> -5x-1=y
For example: x=0
-5*0-1=-1
<u>
</u>